
Factorisons les expressions suivantes :
A=3xy−6y3y est le facteur commun
A=3y×x−2×3y
A=3y(x−2)
B=(x−1)(x+2)+(x−1)(x+3)(x−1) est le facteur commun
B=(x−1)(x+2)+(x−1)(x+3)
B=(x−1)[(x+2)+(x+3)]
B=(x−1)(x+2+x+3)
B=(x−1)(2x+5)
C=(5x+3)(2x−1)−(5x+3)2(5x+3) est le facteur commun
C=(5x+3)(2x−1)−(5x+3)(5x+3)
C=(5x+3)[(2x−1)−(5x+3)]
C=(5x+3)(2x−1−5x−3)
C=(5x+3)(−3x−4)
D=(7x+6)(3x−5)−(3x−5)(3x−5) est le facteur commun
D=(7x+6)(3x−5)−(3x−5)×1
D=(3x−5)[(7x+6)−1]
D=(3x−5)(7x+6−1)
D=(3x−5)(7x+5)
E=15x3z+3xz3xz est le facteur commun
E=3xz×5x2+3xz×1
E=3xz(5x2+1)